The Jarisch-Herxheimer Reaction in a Child with Community-Acquired Pneumonia: a Clinical Case - Vladimir K. Tatochenko; Maya D. Bakradze; Asmik Agaronian (Union of pediatricians of Russia, 2018)
The Jarisch-Herxheimer reaction (JHR) is a shock-like state in response to antimicrobial therapy due to the release of toxins from decomposing microbial bodies. The reaction mainly occurs in patients with spirochetosis, less often in patients with brucellosis, bartonellosis, rickettsiosis, and can be possibly observed in patients with sepsis or meningococcemia. The JHR in children with community-acquired pneumonia has not been previously described. The article provides the author's own observation of a similar reaction in a child with upper lobe pneumonia associated with amoxicillin treatment and resolved after the administration of prednisolone.